Pemberitaan Media Pers Indonesia - Ashadi Siregar (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2006)
New freedom and democratic atmosphere existing in Indonesia allow the Indonesian press enjoys its new significant position. This can expand the Indonesian press goals, particularly in enriching the industrial aspiration of the institution. However, bearing in mind that Indonesia is a multicultural country, the Indonesian press can also strengthen the various demographic backgrounds of the state leading to the unity of Indonesia. This article discusses four points of the Indonesian press that need to he considered by the mass media professionals.